Trade in a ‘Green Growth’ Development Strategy : Global Scale Issues and Challenges - de Melo, Jaime (2013)
This paper surveys the state of knowledge about the trade-related environmental consequences of a country's development strategy along three channels: (i) direct trade-environment linkages (overexploitation of natural resources and trade-related transport costs); (ii) 'virtual trade' in emissions resulting from production activities; and (iii) the product mix attributes of a 'green-growth' strategy (environmentally preferable products and goods for environmental management). Trade exacerbates over-exploitation of natural resources in weak institutional environments, but there is little evidence that differences in environmental policies across countries has led to significant 'pollution havens.' Trade policies to 'level the playing field' would be ineffective and result in destructive conflicts in the World Trade Organization. Lack of progress at the Doha Round suggests the need to modify the current system of global policy making.